Fashion and art - Geczy, Adam; Karaminas, Vicki (Berg, 2012)
Bringing together original, cutting-edge contributions from leading international scholars across a range of disciplines, this book is essential reading for anyone interested in exploring the intersections and changing relationship between fashion and art, past and present.